Analisis Pengaruh Label Halal terhadap Minat Pembelian Produk Kosmetik Wardah - Izzah, Nur (Jurnal Hukum Ekonomi Syariah, 2025)
This study aims to analyze the influence of halal labels, prices, and advertising on purchasing interest in Wardah cosmetic products. The study used a quantitative method with primary data collected through questionnaires from 95 respondents who were academics of the Jakarta Institute of Qur'anic Sciences (IIQ). Data analysis was conducted using multiple linear regression using SPSS version 25. The results showed that partially, halal labels, prices, and advertising had a positive and significant effect on purchasing interest. Simultaneously, the three independent variables also had a significant effect on purchasing interest. These findings confirm that the clarity of halal labels, appropriate pricing, and advertising effectiveness contribute to increasing consumer purchasing interest in halal cosmetic products. Keywords: Halal Label; Price; Advertising; Purchase Interest